V is for Virgins & Vixens - 10 Erotic Short Stories - B., Malva (Saga Egmont, 2023)
Part of the erotic alphabet series, 'V is for Virgins & Vixens - 10 Erotic Short Stories' is a collection of erotica that explores the two sides of a sexual coin; the virgin and the vixen.